Alterations in lipid profiles in children with perinatally acquired HIV infection living in Ghana: A cross-sectional study. - Ruth Ayanful-Torgby; Veronika Shabanova; Akosua Aya Essuman; Emmanuel Boafo; Linda Eva Amoah; Elijah Paintsil (PLoS ONE)
Children and adolescents who acquired HIV perinatally and are on lifelong antiretroviral therapy (ART) are at increased risk of lipid abnormalities, premature atherosclerosis, and early onset cardiovascular diseases (CVD). Majority of these children reside in sub-Saharan Africa, where monitoring of lipid profiles is not routine. In this study, we assessed the age dependent prevalence of dyslipidemia among children and adolescents who acquired HIV in Ghana and explored effects of age and sex. In this cross-sectional study, we examined lipid profiles of 397 children aged 6-18 years. Dyslipidemia was defined by elevated total cholesterol (TC) (≥200 mg/dL) or triglyceride (TG) levels (>150 mg/dL) or low-density lipoprotein cholesterol (LDL-C) (>130 mg/dL) or reduced high-density lipoprotein cholesterol (HDL-C) (<35 mg/dL). In subgroup analyses, dyslipidemia prevalence, by at least one criterion and for each criterion separately, was compared between age groups 6-12 (pre-teen) and 13-18 (teenage) years, as well as by sex, recognizing potential sample size limitations we state our findings and p-values. The overall prevalence of dyslipidemia was 42.32%, and by individual criterion was 9.07% using LDL-C, 11.84% using TC, 15.87% using TG, and 24.00% using HDL-C. Additionally, 5.04% (n = 20) of the participants showed abnormalities across three parameters. Teenagers had a higher overall prevalence of dyslipidemia (46.75% vs. 39.04%, p = 0.12). Criterion-based dyslipidemia prevalence varied across age groups, with TC-based (14.04% vs. 8.88%, p = 0.12) being higher in the pre-teen group, while elevated TG-based (20.12% vs. 12.72%, p = 0.05) and low levels of HDL-based (28.99% vs. 20.60%, p = 0.05) were more prevalent in the teenagers. The mean levels of TC (p = 0.04) and LDL-C (p = 0.03) were significantly higher in the pre-teen age groups. Females had nearly twice as high as that of males with prevalence of abnormal LDL-C levels (11.39% vs. 6.67%, p = 0.13). We observed varying trends in the prevalence of dyslipidemia and lipid profile levels across age and sex groups, likely influenced by developmental and hormonal changes, although most differences were not statistically significant. This study showed a high prevalence of dyslipidemia among children who acquired HIV perinatally and are on ART, with possible age-related and sex variations in lipid profiles likely influenced by developmental and hormonal changes. These findings emphasize the importance of implementing routine monitoring for lipid disorders within this population and further confirmatory investigation of effects of age and sex as these children grow.